1992
DOI: 10.1038/ki.1992.118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of albuminuria in non-insulin-dependent diabetic patients

Abstract: A prospective study of the prevalence and causes of persistent albuminuria (greater than 300 mg/24 hr) was conducted in non-insulin-dependent diabetic (NIDDM) patients, age less than 66 years, attending a diabetic clinic during 1987. All eligible patients (N = 370) were asked to collect at least one 24-hour urine sample for albumin analysis. Urine collection was obtained in 224 males and 139 females (98%). Fifty patients (7 women) suffered from persistent albuminuria (13.8%). The prevalence of albuminuria was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
250
3
6

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(286 citation statements)
references
References 16 publications
25
250
3
6
Order By: Relevance
“…Thus, it is important to define the clinical characteristics and laboratory features to correctly indicate the presence of NDRD and to selectively carry out renal biopsies in those patients. Studies based on renal biopsies in diabetic patients have shown that the incidence of NDRD in patients with type 2 diabetes mellitus was much higher than in patients with type 1 diabetes mellitus14, 21. The incidence of NDRD in the present study was 69.2%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it is important to define the clinical characteristics and laboratory features to correctly indicate the presence of NDRD and to selectively carry out renal biopsies in those patients. Studies based on renal biopsies in diabetic patients have shown that the incidence of NDRD in patients with type 2 diabetes mellitus was much higher than in patients with type 1 diabetes mellitus14, 21. The incidence of NDRD in the present study was 69.2%.…”
Section: Discussionmentioning
confidence: 98%
“…According to current guidelines, the presence of >3 RBCs/hpf is considered clinically significant microscopic hematuria26. There have been various criteria, for both scientific research and the clinical diagnoses of hematuria: >2 RBCs/hpf6, >3 RBCs/hpf14, 15, >5 RBCs/hpf27, >10 RBCs/hpf3, and >15 RBCs/hpf. As a result, the incidence of hematuria varied from 4.9 to 39.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Albuminuria is a marker of renal damage and a hallmark of progression to renal insufficiency [27][28][29]. It increases cardiovascular risk in type 2 diabetes mellitus [30,31], probably because it reflects widespread increased vascular permeability causing organ damage [28,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is greater heterogeneity of structural lesions and GFR in both microalbuminuric and proteinuric type 2 diabetic patients [4,8,12,13]. Some type 2 diabetic patients have a relatively well preserved GFR despite increased proteinuria and blood pressure; this may be related to the more pronounced glomerular enlargement that is seen in these patients [4].…”
Section: Introductionmentioning
confidence: 99%